2014
DOI: 10.1073/pnas.1324194111
|View full text |Cite
|
Sign up to set email alerts
|

A tick-borne segmented RNA virus contains genome segments derived from unsegmented viral ancestors

Abstract: Although segmented and unsegmented RNA viruses are commonplace, the evolutionary links between these two very different forms of genome organization are unclear. We report the discovery and characterization of a tick-borne virus-Jingmen tick virus (JMTV)-that reveals an unexpected connection between segmented and unsegmented RNA viruses. The JMTV genome comprises four segments, two of which are related to the nonstructural protein genes of the genus Flavivirus (family Flaviviridae), whereas the remaining segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
336
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(376 citation statements)
references
References 27 publications
15
336
0
1
Order By: Relevance
“…Occasionally though, more recent transitions are uncovered and analysis of these events provides insight into the macroevolution of RNA viruses. Qin et al (2014) reported just such a connection between segmented and unsegmented RNA viruses by describing a segmented virus (Jingmen tick virus, JMTV) with sequence homology to the Flaviviridae , a large family of vertebrate and invertebrate viruses (including a number of important human pathogens, e.g., Zika, yellow fever, West Nile, dengue, Japanese encephalitis and Hepatitis C viruses) with unsegmented, positive-sense RNA genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally though, more recent transitions are uncovered and analysis of these events provides insight into the macroevolution of RNA viruses. Qin et al (2014) reported just such a connection between segmented and unsegmented RNA viruses by describing a segmented virus (Jingmen tick virus, JMTV) with sequence homology to the Flaviviridae , a large family of vertebrate and invertebrate viruses (including a number of important human pathogens, e.g., Zika, yellow fever, West Nile, dengue, Japanese encephalitis and Hepatitis C viruses) with unsegmented, positive-sense RNA genomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our understanding of arthropods has largely focused on their role as vectors for vertebrate viruses, although this view has recently been challenged by the discovery of phylogenetically divergent arthropod-specific viruses (3,4). The remaining genera in the family-Hepacivirus, Pegivirus, and Pestivirus-are exclusively found in mammals, and their diversity has greatly expanded with recent virus discoveries in various mammalian species, including bats, dogs, horses, pigs, ruminants, and rodents (5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Although GKaV was reported to be a double-stranded RNA (dsRNA) virus (14), the RNA digestion experiment was performed on crude plant extracts where the dsRNA is more likely to be the replication complex rather than the genome itself (15). More remarkable was the recent demonstration that Jingmen tick virus (JMTV) and Toxocara canis larva agent (TCLA) are clearly related to flaviviruses but possess a very different genomic plan comprising four distinct segments (11), in turn raising questions about the evolutionary link between segmented and unsegmented genomes. Since these segmented flavi-like viruses have not been formally classified, we tentatively refer to them as the Jingmenvirus group.…”
mentioning
confidence: 99%
“…Although these insect-specific viruses have no direct impact on public health, they may modulate the transmission of viruses that are pathogenic to vertebrates (3). The development of metagenomic sequencing approaches has therefore led to a reevaluation of the mosquito virome, including the recent discovery of viruses of the families Bunyaviridae (4)(5)(6)(7)(8), Rhabdoviridae (6,(9)(10)(11), Orthomyxoviridae (6,12), Flaviviridae (13)(14)(15), Mesoniviridae (16), and Reoviridae (8,17) as well as of the unclassified Chuvirus (6) and Negevirus (18) groups. In addition, metagenomics surveys have discovered viruses in families not previously known to infect mosquitoes, such as the Iflaviridae, Dicistroviridae, Totiviridae, Chrysoviridae, and Narnaviridae (8,(19)(20)(21)(22).…”
mentioning
confidence: 99%